(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In the last years, the increasing interest in substituting the conventional huge, centralized power generation systems with distributed renewable energy sources has gained more attention; especially the photovoltaic (PV) distributed energy sources due to their various advantages and benefits. Besides, it becomes quite possible to produce a nearly sinusoidal output voltage waveform that satisfies the grid connection criteria by the use of multilevel voltage source inverters at the grid level. These types of inverters have known an important development that offers more advantages in comparison to their counterparts topologies where the produced ac output voltage is made up of several levels of voltages with lower THD content. In this context, a new power conversion structure is applied to the grid-connected photovoltaic systems where the three-phase three-level neutral point clamped (NPC) multilevel inverter is used. The modeling and the control of the grid-connected PV power system are investigated and each component of the system is presented and discussed in detail. The effectiveness of the proposed structure is checked with the obtained simulation results for the whole system using MATLAB/SIMULINK.